Podia histology and ultrastructure of tropical sea cucumber Phyllophorus sp. (Phyllophoridae) and Colochirus quadrangularis (Cucumaridae) from Madura Strait, Indonesia - DWI WINARNI; SIFERA ANGGITA ERIDIANTI; LISTIJANI SUHARGO; FIRAS KHALEYLA; ISMILIANA WIRAWATI (Society for Indonesian Biodiversity, 2023)
Abstract. Winarni D, Eridianti SA, Suhargo L, Khaleyla F, Wirawati I. 2023. Podia histology and ultrastructure of tropical sea cucumber Phyllophorus sp. (Phyllophoridae) and Colochirus quadrangularis (Cucumaridae) from Madura Strait, Indonesia. Biodiversitas 24: 5685-5692. Phyllophorus sp. and Colochirus quadrangularis are sea cucumber species found in Madura Strait, East Java, Indonesia. Both species possess distinctive podia structures, which are protrusions on their body walls resembling spines. These structures serve as tube feet for movement (ventral podia) and sensory organs (dorsal papillae). This research aimed to compare the podia structures of Phyllophorus sp. and Colochirus quadrangularis. Five samples of each species were collected from the Madura Strait. Histological slides were prepared for the papillae (dorsal) and podia (ventral) on the anterior, median, and posterior body sections. Simultaneously, an examination of the ultrastructure was conducted using a scanning electron microscope (SEM). Analysis revealed differences between the podia of the two species. Phyllophorus sp. papillae had semi-flat tips, were non-suckered (SFNS), and exhibited squamous to short columnar epithelia, while their tube feet had flat tips, were non-suckered, and had columnar epithelia. Papillae were denser than tube feet. Conversely, C. quadrangularis papillae were pointed and non-suckered (PNS), and tube feet were flat and non-suckered (FNS). Notably, ossicle-dense areas in C. quadrangularis papillae had a pyramidal shape. In summary, the histology and ultrastructure of podia in these species displayed significant differences, highlighting their unique characteristics. They also imply to the adaptation biology of sea cucumber in Indonesian waters.